Redesigning Public Service: Strengthening the Service Capacity of Public Service Malls through the Malcolm Baldrige Framework - Rohman, Abd.; Setyawan, Dody; Hardianto, Willy Tri (Universitas Muhammadiyah Malang, 2025)
Improving institutional performance is an absolute requirement in improving public service capacity, but Public Service Mall (MPP) often find operational challenges that render them ineffective. This research aims to analyze and describe how to strengthen employee and organizational performance to build a quality MPP in Malang City, going beyond previous studies that focused on implementation, partial effectiveness, or public satisfaction alone. The main problem identified is that the MPP's suboptimal performance is rooted in weaknesses in organizational work patterns such as rigidity, slowness of service processes, and fragmentation of services, which is allegedly not just an issue of individual employee capacity. This research uses a qualitative approach with the Malcolm Baldrige evaluation framework at MPP Malang City, this research collects primary data through purposive interviews with officials, employees, and the community, as well as secondary data in the form of archives and documentation. The results revealed fundamental problems in the dimensions of strategic leadership, quality planning, adaptive human resource management, utilization of data analysis, and integration of cross-agency processes, which caused the focus on meeting the expectations of the community to obtain fast and easy services to be neglected. Systematic adoption of the Baldrige model framework is recommended to strengthen visionary leadership, optimize data-based decisions, scalable planning, revitalize human resources, and redesign integrated processes to realize an efficient and community-oriented MPP.